An online color naming experiment in Russian using Munsell color samples. Issue 3 (17th October 2017) - Paramei, Galina V.; Griber, Yulia A.; Mylonas, Dimitris
Abstract: Russian color naming was explored in a web‐based experiment. The purpose was 3‐fold: to examine (1) CIELAB coordinates of centroids for 12 Russian basic color terms (BCTs), including 2 Russian terms for "blue", sinij "dark blue", and goluboj "light blue", and compare these with coordinates for the 11 English BCTs obtained in earlier studies; (2) frequent nonBCTs; and (3) gender differences in color naming. Native Russian speakers participated in the experiment using an unconstrained color‐naming method. Each participant named 20 colors, selected from 600 colors densely sampling the Munsell Color Solid. Color names and response times of typing onset were registered. Several deviations between centroids of the Russian and English BCTs were found. The 2 "Russian blues", as expected, divided the BLUE area along the lightness dimension; their centroids deviated from a centroid of English blue . Further minor departures were found between centroids of Russian and English counterparts of "brown" and "red". The Russian color inventory confirmed the linguistic refinement of the PURPLE area, with high frequencies of nonBCTs. In addition, Russian speakers revealed elaborated naming strategies and use of a rich inventory of nonBCTs. Elicitation frequencies of the 12 BCTs were comparable for both genders; however, linguistic segmentation of color space, employing a synthetic observer, revealed gender differences in naming colors, with more refined naming of the "warm" colors from females. We conclude that, along with universal perceptual factors, that govern categorical partition of color space, Russian speakers' color naming reflects language‐specific factors, supporting the weak relativity hypothesis.